Towards a consumer sentiment channel of monetary policy - Sebastian Debes; Johannes Gareis; Eric Mayer; Sebastian Rüth (University of Würzburg, Department of Economics, 2014)
We investigate the role of consumer confidence in the transmission of monetary policy shocks from an empirical and theoretical perspective. Standard VAR based analysis suggests that an empirical measure of consumer confidence drops significantly after a monetary tightening and amplifies the impact of monetary policy on aggregate consumption. Using a behavioral DSGE model, we show that a consumer sentiment channel can account for the empirical findings. In an environment of heterogeneous expectations, which gives rise to the notion of consumer sentiment, innovations to the Federal Funds rate impact on consumer confidence and thereby the broader economy.
Keywords: E32; E52; D83; 330; monetary policy; monetary transmission; consumer sentiment